2001
DOI: 10.1007/s001980170072
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment Tool for Predicting Fracture Risk in Postmenopausal Women

Abstract: Due to the magnitude of the morbidity and mortality associated with untreated osteoporosis, it is essential that high-risk individuals be identified so that they can receive appropriate evaluation and treatment. The objective of this investigation was to develop a simple clinical assessment tool based on a small number of risk factors that could be used by women or their clinicians to assess their risk of fractures. Using data from the Study of Osteoporotic Fractures (SOF), a total of 7782 women age 65 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
252
2
24

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(287 citation statements)
references
References 22 publications
9
252
2
24
Order By: Relevance
“…To identify the majority (ie, around 80%) of women who will suffer a fracture, the cutoff has to be raised to 60% (ie, 60% of the population has to be classified as being at high risk). Noteworthy, other investigators reported the lack of sensitivity of FRAX in elderly women (27)(28)(29) and in some male populations. (30) We found that parity, which is not included in the FRAX algorithm, was a significant predictor of the risk of major OP fracture, independent of BMD and of the other CRFs.…”
Section: Discussionmentioning
confidence: 95%
“…To identify the majority (ie, around 80%) of women who will suffer a fracture, the cutoff has to be raised to 60% (ie, 60% of the population has to be classified as being at high risk). Noteworthy, other investigators reported the lack of sensitivity of FRAX in elderly women (27)(28)(29) and in some male populations. (30) We found that parity, which is not included in the FRAX algorithm, was a significant predictor of the risk of major OP fracture, independent of BMD and of the other CRFs.…”
Section: Discussionmentioning
confidence: 95%
“…For this reason, there has been interest in the development of algorithms that express absolute risk, or the probability of fracture within a given time period. (4)(5)(6)(7) The World Health Organization (WHO) Collaborating Center for Metabolic Bone Diseases conducted several metaanalyses of data from large-scale prospective studies in various countries to identify and quantify the risk of fracture associated with several clinical factors (personal history of fracture (8,9) or parental history of fracture, (10) body mass index, (11) smoking, (12) and glucocorticoid treatment (13) ) independent from BMD and age. These extensive studies have contributed to the development of a standardized methodaimed at use in clinical practice-for expressing absolute fracture risk in men and women.…”
Section: Introductionmentioning
confidence: 99%
“…(2)(3)(4) In clinical practice, the physician now can assess the risk of hip fracture for an individual patient from several clinical factors, which include age, weight, fracture after age 50 years, parental hip fracture, smoking status, alcohol intake, glucocorticoid therapy, and secondary causes of osteoporosis, with or without areal bone mineral density (aBMD). (5,6) These variables can be pooled into the recent World Health Organization (WHO) FRAX tool (www.shef.ac.uk/FRAX/) or similar algorithms to calculate a 10-year fracture risk. (7,8) Guidelines for treatment have been published in the United States and Europe, (9)(10)(11) but targeting preventive interventions is still challenging.…”
Section: Introductionmentioning
confidence: 99%